Introduction to the Department of Pediatrics of Shree Birendra Hospital, Chhauni: Then and Now - Neopane, Arun; Shah, Radha; Thapa, Bishnu; Rimal, Hem Sagar (Medical Journal of Shree Birendra Hospital, 2003)
Introduction to the Department of Pediatrics of Shree Birendra Hospital, Chhauni: Then and Now